Structural-magnetic correlations on the first dinuclear spin crossover d(4) system - Goeta, A; Howard, J; Hughes, A; O'Hare, D; Copley, R (2007)
The triple decker dinuclear Cr(ii) salt [(η5-C 5Me5)Cr(μ2:η5-P 5)Cr(η5-C5Me5)]+ (SbF6)- has been structurally characterised by multiple temperature X-ray diffraction experiments from 290 K to 12 K. This material shows changes in its structural features which correlate with its magnetic response, including a structural transition with a change of symmetry from the orthorhombic space group Fddd to the monoclinic I2/a at ∼160 K and an abrupt rearrangement of electron density at ∼23 K This journal is © The Royal Society of Chemistry.